Evaluation of the economic benefits of using Buckling-Restrained Braces in hospital structures located in very soft soils. (1st April 2017) - Guerrero, Héctor; Terán-Gilmore, Amador; Ji, Tianjian; Escobar, José A.
Highlights: The economic benefits of equipping hospital structures with BRBs are evaluated using a rigorous probabilistic approach. The study is focused on hospital structures located on the very soft soils of the lakebed zone of Mexico City. Three-, six- and nine-storey framed buildings in 2D are designed and evaluated. For comparison, five cases defined by the contribution of the BRBs to the strength capacity of the structures, are studied. Several comparisons were conducted, e.g. dynamic responses, probability of collapse, initial cost, and lifecycle cost. The most convenient design options were indentified. Abstract: Since economic quantities are more meaningful to decision makers than dynamic response parameters, this paper examines the economic benefits of using Buckling-Restrained Braces (BRBs) in hospitals located in the very soft soils of the lakebed zone of Mexico City. Since non-structural elements and contents are far more expensive than the structure itself, they are included in detail in the analyses. The results of analyses on three-, six-, and nine-storey frames, which represent short-period structures, show that the expected (or probable) losses and lifecycle costs are smaller when structures are equipped with BRBs. Different cases (defined by the contribution of the BRBs to the strength capacity of the structure) were analysed and compared. The best design options were identified from a comparison of lifecycle costs. As an example, a comparison of cost-benefit analysis between a bare frame and a frame designed under gravity loads and equipped with BRBs, shows that the latter is more economical; because, for the same initial cost, the lifecycle costs are significantly smaller.